WASTE COLLECTORS COOPERATIVES AND REVERSE LOGISTICS NETWORKS: DOUBLE CASE STUDY - Almeida, Francieli Aparecida de; Viana, Ana Paula Severo; Ritter, Ágata Maitê; Sellitto, Miguel Afonso (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The objective of the article was to analyze the functioning of two cooperatives that provide processed waste required by industries in the city of São Leopoldo, RS. The research method was the double case study. Two out of the six cooperatives in operation in the city were studied. Documentation of the cooperative and produced by the municipal public authority were consulted, non-participant observations and interviews with the Presidents of cooperatives were made. One of the cooperatives receives only materials from selective collection, while the other receives the entire home collection. The cooperative that receives selected stuff, despite being more recent and less structured, provides more income to their members. The material recovered by both cooperatives is sold to intermediaries who give scale to the operation and sell to industry as recovered raw material. It was concluded that the role of cooperatives in the reverse chain is to retrieve post-consumer materials and act as a supplier of raw materials for industry. Additionally, cooperatives play social role to low-income communities, by providing jobs and income alternatives, and environmental role, by contributing to the reduction of pressure on landfills and incineration of municipal solid waste.